False negative results in glaucoma detection with Heidelberg Retina Tomograph II - Catherine Deghislage; Lidwine Van Malderen; Thierry G Zeyen (Clinical Ophthalmology, 2008)
Catherine Deghislage, Lidwine Van Malderen, Thierry G ZeyenDepartment of Ophthalmology, University Hospitals, Leuven, B-3000, BelgiumPurpose: To evaluate the rate of false negative results with the Heidelberg Retina Tomograph (HRT II) in a glaucoma practice.Design: Cross-sectional study.Methods: We analyzed the HRTs taken between October 2002 and October 2003 in our glaucoma clinic, and selected the patients who had a good quality image (SD < 40 µ) with a normal Moorfield’s Regression Analysis (MRA). A masked independent observer classified those patients as normal, glaucoma suspect, or glaucomatous on the basis of optic disc stereo photos (ODP) and at least 2 consecutive reliable automated perimetries. The diagnosis of glaucoma was based on a glaucomatous optic disc with a congruent, reproducible visual field defect.Results: Four hundred and fifty patients who had undergone an HRT examination were analyzed. One hundred and nine patients had an HRT classified as normal on the MRA, and a good quality image. Fifteen of those 109 patients (13.7%) were classified as glaucomatous on the basis of an abnormal ODP with corresponding visual field defect. Seven (6.4%) patients were classified as glaucoma suspect.Conclusion: Fourteen percent of glaucoma patients with glaucoma remained undetected with the HRT II Moorfield’s regression analysis as a sole means to detect glaucoma.Keywords: glaucoma detection, false negative results, Heidelberg Retina Tomograph II